Long range based effective field monitoring system - Popuri Rajani Kumari; Chalasani Suneetha; Vadlamudi Sri Lakshmi; Nakka Rama Priya; Bodapati Venkata Rajanna; Ambarapu Sudhakar (Institute of Advanced Engineering and Science, 2024)
Adoption of the internet of things (IoT) is moving forward quickly because of the developments in communication protocols and technology involving sensors. The IoT is promoting real-time agricultural field monitoring from any distant place. For the IoT to be implemented effectively there are a number of agricultural issues related to less power usage and long-distance transfer of data are to be addressed. By using LoRa, which is a wireless communication system for IoT applications, these difficulties can be avoided when sending information from fields of crops to a web server. Acustomized sensor node and LoRa are used in this work to transmit continuously updated information to a remote server. Monitoring the quality of water, and reducing wasteful use of water are the main goals.